PEMBARUAN DAN PERAN SOSIAL TRANSFORMATIF PESANTREN DAN ISLAM INDONESIA - Achmad Maulani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Discuss about Islam in Indonesia is inseparate from the discourse about pesantren and Nahdatul Ulama. Both entities are an Islamic group that has contributed signifiantly for the dynamics of Indonesian Islam . Pesantren and Nahdatul Ulama have dialogued with social culture of society through the local wisdom in pesantren. Pesantren is the real face of Islam in Indonesia. This paper want to discuss about the dynamics and socially transformative role of pesantren in Indonesia